First-Principles Study of Structural, Electronic and Magnetic Properties of Lithium Doped Hexa]gonal Boron Nitride Monolayer (h-BN) - Khanal, K.; Acharya, D.; Pantha, N.; Adhikari, N. P. (Journal of Nepal Physical Society, 2023)
We examine the structural, electronic, and magnetic properties of pure and lithium doped hexagonal boron nitride (h-BN) monolayer using density functional theory (DFT) based on first-principles calculations. LiB site is more conducive to doping than LiN site, according to the values of formation energy, which are found to be 13.06 eV and 18.50 eV, respectively. Metallic behavior may be seen in the band structures for both the LiB site and LiN in nature. At both sites, the density of states (DOS) is asymmetric for spin-up and spin-down electrons. This suggests that systems with Li doping on h-BN are magnetic.